2013
DOI: 10.1371/journal.pone.0065373
|View full text |Cite
|
Sign up to set email alerts
|

Promoter DNA Methylation Pattern Identifies Prognostic Subgroups in Childhood T-Cell Acute Lymphoblastic Leukemia

Abstract: BackgroundTreatment of pediatric T-cell acute lymphoblastic leukemia (T-ALL) has improved, but there is a considerable fraction of patients experiencing a poor outcome. There is a need for better prognostic markers and aberrant DNA methylation is a candidate in other malignancies, but its potential prognostic significance in T-ALL is hitherto undecided.Design and MethodsGenome wide promoter DNA methylation analysis was performed in pediatric T-ALL samples (n = 43) using arrays covering >27000 CpG sites. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 48 publications
6
81
1
Order By: Relevance
“…Our results showed the vast majority of CpGs in SDHB-related PPGLs were hypermethylated and verify previous reports suggesting high-CIMP (2,8). A wide variety of human neoplasms have been described with high-CIMP (21)(22)(23). Prognosis associated with high-CIMP is cell-typedependent.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed the vast majority of CpGs in SDHB-related PPGLs were hypermethylated and verify previous reports suggesting high-CIMP (2,8). A wide variety of human neoplasms have been described with high-CIMP (21)(22)(23). Prognosis associated with high-CIMP is cell-typedependent.…”
Section: Discussionsupporting
confidence: 90%
“…Prognosis associated with high-CIMP is cell-typedependent. In glioblastoma and pediatric T-cell acute lymphoblastic leukemia, high-CIMP is associated with a more favorable prognosis, whereas poor prognosis has been reported for neuroblastoma and PPGL (2,(21)(22)(23). SDHx PPGLs, particularly SDHBrelated have a higher risk to develop metastatic disease (24).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have suggested that methylation levels at diagnosis may predict outcome in some ALL patients [23][24][25][26] and Yang and colleagues demonstrated that residual DNA methylation at the p73 locus at remission can be used for detection of MRD [27], but this is the first study to find evidence that remission-specific methylation patterns, unrelated to residual disease, may predict subsequent patient outcome. Patients who survived long-term (> 5 years) generally exhibited remission methylation levels at or near the level of healthy controls.…”
Section: Discussionmentioning
confidence: 93%
“…Recent advances in technology have allowed genome-wide profiling of epigenetic status in childhood ALL. For example, Borssen et al examined the relationship between methylation status and clinical outcomes and found that based on CpG island methylator phenotype (CIMP), childhood T-cell ALL patients classified as CIMP-negative (low methylation) had significantly poorer outcomes [40]. Feng et al examined the genome-wide DNA methylation profiles of B-cell ALL and also discovered a DNA methylation signature predictive of relapse in pediatric patients [41].…”
Section: Epigenetic Deregulation In Childhood Cancersmentioning
confidence: 99%